Meta-analysis of genome-wide association studies for circulating phylloquinone concentrations(1)(2)(3)(4)(5) - Dashti, Hassan S (Am J Clin Nutr, 2014)
Background: Poor vitamin K status is linked to greater risk of several chronic diseases. Age, sex, and diet are determinants of circulating vitamin K; however, there is still large unexplained interindividual variability in vitamin K status. Although a strong genetic component has been hypothesized, this has yet to be examined by a genome-wide association (GWA) study. Objective: The objective was to identify common genetic variants associated with concentrations of circulating phylloquinone, the primary circulating form of vitamin K. Design: We conducted a 2-stage GWA meta-analysis of circulating phylloquinone in 2 populations of European descent from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium Nutrition Working Group. Circulating phylloquinone was measured by using reversed-phase high-performance liquid chromatography. Results from adjusted cohort-specific discovery GWA analyses were meta-analyzed with inverse variance weights (n = 2138). Associations with circulating phylloquinone at P < 1 × 10(−6) were then evaluated in a second-stage analysis consisting of one independent cohort (n = 265). Results: No significant association was observed for circulating phylloquinone at the genome-wide significance level of 5 × 10(−8). However, from the discovery GWA, there were 11 single-nucleotide polymorphism (SNP) associations with circulating phylloquinone at P < 1 × 10(−6), including a functional variant previously associated with warfarin dose and altered phylloquinone metabolism. These SNPs are on 5 independent loci on 11q23.3, 8q24.3, 5q22.3, 2p12, and 19p13.12, and they fall within or near the candidate genes APOA1/C3/A4/A5 cluster (involved in lipoprotein metabolism), COL22A1, CDO1, CTNAA2, and CYP4F2 (a phylloquinone oxidase), respectively. Second-stage analysis in an independent cohort further suggests the association of the 5q22.3 locus with circulating phylloquinone (P < 0.05). Conclusions: Multiple candidate genes related to lipoprotein and vitamin K metabolism were identified as potential determinants of circulating phylloquinone. Further investigation with a larger sample is warranted to verify our initial findings and identify other loci contributing to circulating phylloquinone. Trials related to this study were registered at clinicaltrials.gov as NCT00005121 (Framingham Offspring Study) and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).